2015
DOI: 10.1007/s40124-014-0072-6
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Transition to Adult Care for Young People with Chronic Kidney Disease

Abstract: The transition from pediatric-to adult-oriented care typically occurs during emerging adulthood, a developmental stage during which the risks of poor treatment adherence and adverse outcomes are elevated. Inadequate support during this change in care environment may augment the risks. With a focus on chronic kidney disease, we will briefly review the evidence linking transition from pediatric-to adult-oriented care to adverse medical, social, and quality of life outcomes, and outline potential reasons for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 94 publications
0
2
0
Order By: Relevance
“…A failure to transfer AYAs using carefully planned, well-designed, feasible transition programmes and interventions with the required competencies to manage their condition, may lead to poor attendance at adult nephrology units ( Çiçek & Alpay, 2022 ). In turn, AYAs are placed at high risk of clinical deterioration, resulting in a cascade of negative health outcomes ( Foster & Bell, 2015 ; Kreuzer et al, 2019 ; Prüfe et al , 2022 ; Watson et al, 2011 ). This may be attributed to multiple factors and not exclusively poor attendance to adult clinics, such as non-adherence to medications or medical treatment and regimens, including non-adherence to life-long immunosuppressive regimens, leading to an increased risk of rejection and allograft loss and oftentimes a return to dialysis ( Akchurin et al, 2014 ; Campbell et al, 2016 ; Crawford et al, 2020 ; Dobbels et al, 2010 ; Dobbels et al, 2009 ; Foster, 2015 ; Foster & Bell, 2015 ; Kreuzer et al, 2019 ; Mazzucato et al, 2018 ; Prüfe et al ., 2022 ; Quaglia et al, 2014 ; Wildes et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A failure to transfer AYAs using carefully planned, well-designed, feasible transition programmes and interventions with the required competencies to manage their condition, may lead to poor attendance at adult nephrology units ( Çiçek & Alpay, 2022 ). In turn, AYAs are placed at high risk of clinical deterioration, resulting in a cascade of negative health outcomes ( Foster & Bell, 2015 ; Kreuzer et al, 2019 ; Prüfe et al , 2022 ; Watson et al, 2011 ). This may be attributed to multiple factors and not exclusively poor attendance to adult clinics, such as non-adherence to medications or medical treatment and regimens, including non-adherence to life-long immunosuppressive regimens, leading to an increased risk of rejection and allograft loss and oftentimes a return to dialysis ( Akchurin et al, 2014 ; Campbell et al, 2016 ; Crawford et al, 2020 ; Dobbels et al, 2010 ; Dobbels et al, 2009 ; Foster, 2015 ; Foster & Bell, 2015 ; Kreuzer et al, 2019 ; Mazzucato et al, 2018 ; Prüfe et al ., 2022 ; Quaglia et al, 2014 ; Wildes et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of an effective transition programme, incorporating well-planned interventions and strategies for young people living with renal disorders is apparent. Studies have demonstrated that the highest rate of kidney transplant loss occurs during the transition years and immediately following transfer of care ( Foster, 2015 ; Foster & Bell, 2015 ; Kreuzer et al, 2019 ; Prüfe et al , 2022 ; Watson et al, 2011 ). Therefore, this age group must be carefully managed, as graft failure often requires a return to dialysis, reducing the patient’s quality of life, increasing morbidity and mortality rates, shortening AYAs life expectancy, and heightening health care expenses ( Prüfe et al ., 2022 ).…”
Section: Introductionmentioning
confidence: 99%